2015
DOI: 10.1002/jmv.24345
|View full text |Cite
|
Sign up to set email alerts
|

Origin and evolution of Nipah virus

Abstract: Nipah virus, member of the Paramyxoviridae family, is classified as a Biosafety Level-4 agent and category C priority pathogen. Nipah virus disease is endemic in south Asia and outbreaks have been reported in Malaysia, Singapore, India, and Bangladesh. Bats of the genus Pteropus appear to be the natural reservoir of this virus. The aim of this study was to investigate the genetic diversity of Nipah virus, to estimate the date of origin and the spread of the infection. The mean value of Nipah virus N gene evolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 46 publications
2
34
1
Order By: Relevance
“…Many of the pigs were initially infected by eating fruits that were partially eaten by fruits bats, which had left their virus-laden saliva behind (4)(5)(6). Upon isolation and sequencing of the virus, it was revealed that the culprit was a novel RNA virus from Paramyxoviridae family, which includes the Hendra (HeV), mumps (MuV), and measles (MeV) viruses [4][5][6][7]. The symptoms for Nipah infections often include an initial flu-like fever that often follows by irritations, coma, and then death.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the pigs were initially infected by eating fruits that were partially eaten by fruits bats, which had left their virus-laden saliva behind (4)(5)(6). Upon isolation and sequencing of the virus, it was revealed that the culprit was a novel RNA virus from Paramyxoviridae family, which includes the Hendra (HeV), mumps (MuV), and measles (MeV) viruses [4][5][6][7]. The symptoms for Nipah infections often include an initial flu-like fever that often follows by irritations, coma, and then death.…”
Section: Introductionmentioning
confidence: 99%
“…In 2001, a different NiV strain was observed in Bangladesh [4]. There were outbreaks in India or Bangladesh each year thereafter.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, our molecular evidence points to a long history of human–bat cohabitation in Bangladesh with a bat population that has increased steadily over time. While it is difficult to reconstruct the deep evolutionary history of NiV from small gene fragments due to homoplasy and the rapid evolution of RNA viruses (Lo Presti et al, ), it is plausible that bat–human viral spillover events have been part of human history in the region for some time and only recently appreciated due to increased surveillance efforts. A spatial analysis of NiV spillover in Bangladesh supports this assumption, with 45% of the variance in the number of spillover events per district explained by the distance to the nearest NiV surveillance hospital (Cortes et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…space state modelling) to reconstruct cross-species transmission events. The latter can be particularly useful to also discriminate between recent cross-species transmissions, many of which may result in dead-end infections, and host shifts that reflect successful onwards transmission in the new host species.[9,81,9799]4. what are the potential modes of transmission/transmission pathways?studies of the presence of pathogen in different body fluids/excreta can identify or confirm zoonotic sources of infections and indicate unconventional or previously unknown transmission pathways aiding the understanding of transmission pathways and providing focus for epidemiological studies.[100102]experimental infections can demonstrate potential for alternative pathways that may not have been considered, and may identify which modes of transmission are most important.[49,103,104]5.…”
Section: Disentangling and Quantifying Transmissionmentioning
confidence: 99%
“…The difficulty here is that surveillance and reporting of animal diseases is often poor, especially in wildlife but also in livestock diseases in many countries. For many diseases with animal reservoirs of infection, occasional spillover into the human population is often the only indication of ongoing and poorly understood epizootic or enzootic transmission, as we have seen with outbreaks of Ebola [131] and Nipah virus [99]. …”
Section: Disentangling and Quantifying Transmissionmentioning
confidence: 99%